ANALYSIS OF REVERSE SALIENCE SUBSYSTEMS IN COMPOSITE PANELS INDUSTRY AND PERSPECTIVES OF PERFORMANCE GAP METHODOLOGY AS A TECHNOLOGY FORECASTING TOOL - Liliya Hogaboam, Liliya Hogaboam; Jay Justice, Jay Justice (Forestry, Forest, Paper and Woodworking Industry, 2024)
The paper describes the concept of reverse salience subsystems and identifies some possible reverse salients in composite panels industry. The forecasting methodology of measuring the performance gap among the subsystems is suggested for further applications in wood products industry. If the weakest links are identified early during the system’s development, those reverse salients that prevent the development of the technological system could be corrected, or new strategic directions could be established according to a developing situation.